Immune response to recombinant Burkholderia pseudomallei FliC - Koosakulnirand, Sirikamon; Phokrai, Phornpun; Jenjaroen, Kemajittra; Roberts, Rosemary A.; Utaisincharoen, Pongsak; Dunachie, Susanna J.; Brett, Paul J.; Burtnick, Mary N.; Chantratita, Narisara (PloS one, 2018)
Burkholderia pseudomallei is a flagellated Gram-negative bacterium which is the causative agent of melioidosis. The disease poses a major public health problem in tropical regions and diabetes is a major risk factor. The high mortality rate of melioidosis is associated with severe sepsis which involves the overwhelming production of pro-inflammatory cytokines. Bacterial flagellar protein (flagellin) activates Toll-like receptor 5 (TLR5)-mediated innate immune signaling pathways and induces adaptive immune response. However, previous studies of TLR5 signaling in melioidosis have been performed using recombinant flagellin from Salmonella Typhimurium instead of B. pseudomallei. This study aimed to investigate human innate immune response and antibody response against a recombinant B. pseudomallei flagellin (rFliC). We prepared B. pseudomallei rFliC and used it to stimulate HEK-BlueTM-hTLR5 and THP1-DualTM cells to assess TLR5 activation. Subsequently, whole blood stimulation assays with rFliC were performed ex vivo. TLR5-flagellin interactions trigger activation of transcription factor NF-κB in HEK-BlueTM-hTLR5 cells. Pro-inflammatory cytokine (IL-1β, IL-6, and TNF-α) productions from whole blood in response to rFliC differed between fourteen healthy individuals. The levels of these cytokines changed in a dose and time-dependent manner. ELISA was used to determine rFliC-specific antibodies in serum samples from different groups of melioidosis patients and healthy subjects. IgG antibody to rFliC in melioidosis patients with diabetes were higher compared with non-diabetic patients. Our results show that B. pseudomallei flagellin is a potent immune stimulator and that the immune responses to rFliC are different among individuals. This may provide valuable insights toward the potential use of rFliC in vaccine development.